Inside Back Cover: Design Principles for Peptide‐Amphiphile‐Induced Liposomal Receptor‐Targeting with Intracellular Thermosensitivity (ChemNanoMat 1/2016). Issue 1 (17th December 2015) - Shroff, Kamlesh; Liu, Dalong; Aravalli, Rajagopal N.; Forster, Colleen L.; Pengo, Thomas; Sanders, Mark A.; Ebbini, Emad S.; Kokkoli, Efrosini
Abstract : Stealth liposomes were combined with single‐tail peptide‐amphiphiles that provided receptor‐specific binding and cell internalization while also inducing the thermosensitive properties of the liposomes. The resulting peptide‐functionalized liposomes, featured on the Inside Back Cover, outperformed commercially available thermosensitive formulations in terms of cell binding and intracellular temperature‐triggered release in vitro, and showed increased release in vivo after treating the liver of a mouse with mild hyperthermia via a dual‐mode ultrasound array. More details can be found in the Communication by E. S. Ebbini, E. Kokkoli et al. onpage 42 in Issue 1, 2016 (DOI:10.1002/cnma.201500138 ).